2018
DOI: 10.1108/jeim-08-2017-0118
|View full text |Cite
|
Sign up to set email alerts
|

The effects of using social network sites on academic performance: the case of Qatar

Abstract: Purpose Social network sites (SNSs) have been common applications attracting a large number of users in Qatar. Current literature remains inconclusive about the relationship between SNS usage and users’ academic performance. While one stream confirms that SNS usage may lead to addiction and seriously affect individuals’ academic performance, other studies refer to SNS as learning enablers. The purpose of this paper is twofold: first, it investigates the SNS usage profiles among the young generation in the Gulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 60 publications
1
40
0
5
Order By: Relevance
“…Although some earlier researchers have suggested that task distraction is directly linked to SNSA (see e.g. Al‐Yafi et al, ; Liu et al, ), there is limited evidence of the role of mediators associated with techno‐stress, that is envy, social anxiety and rumination. This study, however, contends that SNSA stimulates envy that enhances task distraction among nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some earlier researchers have suggested that task distraction is directly linked to SNSA (see e.g. Al‐Yafi et al, ; Liu et al, ), there is limited evidence of the role of mediators associated with techno‐stress, that is envy, social anxiety and rumination. This study, however, contends that SNSA stimulates envy that enhances task distraction among nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Al‐Yafi, El‐Masri, and Tsai () argued that alongside other reasons, SNSA could lead to task distraction due to a condition called ‘techno‐stress’, the stress caused by use of technology like social networking site. Three common mental states closely linked to techno‐stress are envy (Chow & Wan, ), social anxiety (Butler et al, ) and rumination (Connolly & Alloy, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study on medical students showed that students who used social networks and internet more than average had a poor academic achievement and low level of concentration in the classroom [36]. The results of another study on Qatari students showed that Grade Point Average (GPA) was lower among students who were addicted to social networking compared to other students [37]. The results of a study in India showed that internet and social networking addiction had a negative effect on academic performance and mental health of students [38].…”
Section: Introductionmentioning
confidence: 99%
“…There is no doubt that SNS have gained wider acceptability, usability and have probably become the most important communication tool among university students [1,2,3]. Many researchers have tried to identify SNS's addiction.…”
Section: Introductionmentioning
confidence: 99%